2020
DOI: 10.31851/jmwe.v16i4.3728
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Pengembangan Karir Dan Iklim Organisasi Terhadap Kepuasan Kerja Karyawan Pada PT.PLN (Persero) UIW,S3JB UP 3 Lahat

Abstract: Penelitian ini bertujuan untuk mengetahui Pengaruh pengembangan karir dan iklim organisasi terhadap kepuasan kerja karyawan pada PT. PLN (PERSERO) UIW, S3JB UP 3 Lahat, jumlah responden didalam penelitian ini sebanyak 40 orang, Metode analisis yang digunakan adalah analisis diskriptif kuantitatif dan kualitatif, Analisis diskriptif Kualitatif yaitu dengan membanding antara teori dan kenyataan yang ada sedangkan analisis kuantitatif adalah analisis dengan menggunakan perhitungan statistik. Teknik pengumpulan da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of this research are also in line with the research of Hadjri et al (2019), Setiawan et al (2021) and Cik (2021) who also found a positive and significant effect of training on employee performance. However, there are previous studies that are not in line, namely Syahputra (2020), Andayani (2020) and Lubis et al (2023) who found that training did not have a significant effect on employee performance.…”
Section: Discussionmentioning
confidence: 91%
“…The results of this research are also in line with the research of Hadjri et al (2019), Setiawan et al (2021) and Cik (2021) who also found a positive and significant effect of training on employee performance. However, there are previous studies that are not in line, namely Syahputra (2020), Andayani (2020) and Lubis et al (2023) who found that training did not have a significant effect on employee performance.…”
Section: Discussionmentioning
confidence: 91%